Understanding systemic risk in global financial markets - Aron Gottesman (Wiley, 2024)
Understanding Systemic Risk in Global Financial Markets offers an accessible yet detailed overview of the risks to financial stability posed by financial institutions designated as systemically important. The types of firms covered are primarily systemically important banks, non-banks, and financial market utilities such as central counterparties. Written by Aron Gottesman and Michael Leibrock, experts on the topic of systemic risk, this vital resource puts the spotlight on coherency, practitioner relevance, conceptual explanations, and practical exposition.